BIBLIOMETRIC ANALYSIS OF POSTGRADUATE THESES ON LOCAL POLITICS IN TURKEY (Third Sector Social Economic Review, 2025)
Local politics is a discipline that enables local actors to effectively make and implement decisions. The process of localization, which has gained more value with the globalization process in the world and in Turkey, has given local politics a much greater importance in the eyes of the society. As a reflection of this process, the number of studies on local politics has increased especially in Turkey in the 2000s. Graduate theses have an important place in these studies. The aim of this study is to examine the postgraduate theses on “local politics” in Turkey. There are 52 postgraduate theses on local politics between 1993 and 2024. A bibliometric analysis of the type, year of publication, language of writing, universities and institutes, supervisor titles, number of pages, keywords, research and data collection methods of these theses was conducted. In the analysis, it was determined that the theses on local politics focused on the place of women in local politics, decision-making processes in local politics, participation and representation in local politics.  The majority of the theses are master's theses. It is seen that there is a significant increase in the number of theses as we approach the present day.
Keywords: Local politics; Local authorities; Turkey; Graduate theses; Bibliometric analysis